Effects of taking a nap or break immediately after night shift on nurses’ fatigue recovery and sleep episodes: a quasi-experimental study - Issei Konya; Inaho Shishido; Kazuhiro Watanabe; Masayuki Ikebuchi; Toshiyasu Tanaka; Hisao Kataoka; Rika Yano (Journal of Physiological Anthropology)
Abstract Background Excessive fatigue, sleep deprivation, and poor intershift recovery after night shifts are associated with an increased risk of traffic accidents and maladaptive chronic fatigue. However, little is known about whether taking a nap or break immediately after a night shift improves fatigue recovery and sleep among nurses. This study aimed to examine the effects of taking a 30-min nap or break immediately after a 16-h night shift on fatigue recovery and sleep episodes among nurses. Methods A quasi-experimental crossover study was conducted with 62 nurses who worked 16-h night shifts. Nurses were randomly assigned to two condition sequences (AB or BA): (A) intervention (the nurses took a 30-min nap or break in a nap environment control system after a night shift) and (B) control (the nurses went home as usual after a night shift). Fatigue was measured immediately after the night shift, after taking a nap or break, and after getting up from nighttime sleep on the day after the night shift. Sleep episodes were assessed using a wearable device. Outcomes were compared between the two conditions. Results In the intervention condition, fatigue immediately after the night shift was significantly reduced by taking a nap or break, with a large effect size. Recovery from “local pain or dullness,” one of the symptoms of work-related fatigue, was significantly higher in the intervention than control condition. Compared to the control condition, the intervention condition significantly delayed the timing of the first sleep episode, whereas no significant differences were observed in the main sleep parameters. Conclusions Taking a nap or break immediately after the night shift could be a countermeasure to address fatigue/sleep-related problems among nurses. For nursing managers, encouraging nurses to take a nap or break immediately after the night shift could be a viable option in comprehensive fatigue risk management. Therefore, appropriate napping environments should be installed in clinical settings. Trial registration: UMIN000038444 (date of registration: 30 Oct 2019)